Two scheduling algorithms for input-queued switches guaranteeing voice QoS - Min Song; Alam, M. (2001 IEEE Global Telecommunications Conference - Globecom, 2001)
To support the exponentially increasing demand with quality of service (QoS) requirements, input queued switches show great promise. Scheduling algorithms for input-queued switches must provide high throughput, individual flow QoS guarantee; and high network utilization. Most existing algorithms cannot satisfy the above three tasks. Based on a well-known scheduler, longest port first (LPF), this paper presents two algorithms, (i) worst-case LPF (WLPF), and (ii) prioritized LPF (PLPF), that support voice traffic QoS under the bursty and hot-spot traffic stream. Simulation results are presented that show that both of them improve the voice traffic QoS.